Influence of Social Media Exposure on Knowledge and Behaviour of COVID-19 Preventive Measure - Putu Ayu Indrayathi; Putu Erma Pradnyani; Pande Putu Januraga; Luh Putu Sinthya Ulandari; Laszlo Robert Koloszvari; Benny Tjahjono; Desak Putu Yuli Kurniati; Monika Sri Yuliarti (Intelektual Pustaka Media Utama, 2022)
A lot of misinformation about COVID-19 on social media possibly hinder the practice of healthy behaviors that are essential to protect individuals. This situation is exacerbated by the lack of health literacy in Indonesia. This study aimed to determine the influence of social media information exposure on the knowledge and behavior of Indonesians in compliance with COVID-19 protocols. An online survey of 909 people was conducted from July 2nd to August 10th, 2020. The data collected were knowledge and behavior of preventing COVID-19, while independent variables were socio-demographic characteristics and exposure to social media information. Inclusion criteria were defined as follows: minimum age of 18 years and domiciled in the country during the data collection period. The analysis used for the data collected were univariate and multivariate. The result showed that gender, age, marital status, and social media presence significantly affect a person's knowledge about COVID-19 with a p-value of 0.05. Enforcement behavior of health and healthy living protocols is significantly influenced by the respondent’s gender, marital status, education level, the island of residence, and exposure to online information. The frequency of exposure to information affects people's knowledge and behavior to implement health protocols and healthy living in the COVID-19 era, and it is further influenced by socio-demographic characteristics.